PENERAPAN MODEL PEMBELAJARAN SAVI BERBANTUAN E- MODUL INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI IKATAN KIMIA KELAS X IPA SMA MUHAMMADIYAH 1 PEKANBARU - Sari, Mega Wulan; M.Noer, Asmadi; Haryati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research aims to improve student learning outcomes in chemical bonding material in class X MIPA SMA Muhammadiyah 1 Pekanbaru. This type of research is experimental research with a pretest-posttest design. Sample selection was carried out using a homogeneity test so that the samples obtained from the research were students in class X IPA 3 as the experimental class and students in class X IPA 4 as the control class. The experimental class applied the SAVI learning model while the control class was given learning without SAVI The research results show that learning using the SAVI learning model assisted by interactive e-modules can have a positive influence on student learning outcomes. The results of the research that have been carried out can be concluded that the application of the SAVI learning model assisted by interactive e-modules in the experimental class obtained higher learning outcomes than the control class that applied the scientific model, the difference in the increase in student learning outcomes in the experimental class and the control class obtained an average score of 63.19 or 63.19% in the experimental class with a fairly effective category while in the control class the average was 3.89 0r 3.89% in SAVI learning model assisted by interactive e-modules is quite effective in improving student learning outcomes in chemical bonding material.Key Words: SAVI (Somatic, Audiotory, Visual and Intellectual), Interactive E-module,Learning Outcomes, Chemical Bonds